Mitigation of pesticide residue levels in the exposed dermal regions of occupationally exposed farmworkers by use of personal protective equipment - Lari, Summaiya; Vanka, Janardhan; Jee, Babban; Pandiyan, Arun; Yamagani, Praveen; Kumar, Senthil Balakrishnan; Naidu, Mohan; Jonnalagadda, Padmaja (Frontiers in Public Health, 2023)
Unsafe pesticide handling practices with limited use of personal-protective-equipment (PPE) by the Indian farming groups lead to increased risk of exposure to pesticides. Therefore a community-based follow-up study based on dosimeter, wipes, and hand washing techniques was carried out to evaluate the dermal exposure to pesticides and to analyze the impact of the usage of PPE on minimizing the exposure among the farm-workers of Rangareddy district, India. Risk in terms of hazard quotient (HQ), hazard index (HI), and safety analysis as margin of safety was assessed. Farm-workers averaged 18 years of farming experience and showed resistance to adopting good agricultural practices. Ten pesticide residues were detected in the concentration ranging from 0.000 to 246 mg mL-1 in hand washings, 0.000 to 198.33 ng cm-2 in patch dosimeter, and 0.000 to 1740 ng cm-2 in wipe samples collected from the farm-workers not using PPE. The second phase includes intervention study results that revealed a significant reduction both in the concentrations and the number of pesticide residues detected in the hand washings, patch, and wipe samples of the farm-workers who have used PPE provided to them (p<0.01). Further, the probabilistic health risk assessment in terms of HQ values ranged from 0.02 to 1029.82 and HI was greater than 1, suggesting the non-carcinogenic risks associated with dermal exposure to pesticides among them. Additionally, the safety risk assessment in terms of the margin of safety (MOS) suggests that they follow risky handling practices. The study confirms that farm-workers are exposed to pesticides and emphasizes the significance of using PPE in reducing the risk.